About Some Mental Characteristics of Pseudo-Men and Pseudo-Women - Hošek, Ankica; Momirović, Konstantin; Savić, Maja (Zbornik Instituta za kriminološka i sociološka istraživanja, 2005)
From the population of pupils of high schools in Serbia, age of 18, set of 3599 subjects of both sexes was selected as a two-stage sample. Under the standard conditions, the subjects were set the battery of measuring instruments. From these results the variables for estimation of cognitive and conative characteristics, level of socialization and intensity of aberrant behavior were derived. On the basis of these results and information on sex of subjects, one neural network classified the subjects into two taxons in such way that these taxons correspond as good as possible to biological sex of subjects. The coefficient of efficiency of that classification was .947. On the basis of their psychological profiles neural network classified set of 833 subjects as not belonging to their own biological sex and they were treated as subset of pseudo-men i.e. subset of pseudo-women. In order to identify the psychological profile and study the differences between these subsets, the results were analyzed by canonical discriminative analysis. It was found that although pseudo-men are more similar to women than to real men, and pseudo women are more similar to men than to real women, between pseudo-men and pseudo-women exist substantial and important differences that can be attributed to higher degree of disturbance of conative functions of pseudo-men and better efficiency of parallel processor of pseudo-women. Besides that, pseudo-men have systematically lower results on tests of socialization, but in spite of that, lower degree of global aberrant behavior comparing to pseudo-women.